Gestational diabesity and foetoplacental vascular dysfunction - Cornejo, Marcelo; Fuentes, Gonzalo; Valero, Paola; Vega, Sofía [UNESP]; Grismaldo, Adriana; Toledo, Fernando; Pardo, Fabián; Moore-Carrasco, Rodrigo; Subiabre, Mario; Casanello, Paola; Faas, Marijke M; van Goor, Harry; et al. (Wiley, 2021)
Gestational diabetes mellitus (GDM) shows a deficiency in the metabolism of D-glucose and other nutrients, thereby negatively affecting the foetoplacental vascular endothelium. Maternal hyperglycaemia and hyperinsulinemia play an important role in the aetiology of GDM. A combination of these and other factors predisposes women to developing GDM with pre-pregnancy normal weight, viz. classic GDM. However, women with GDM and prepregnancy obesity (gestational diabesity, GDty) or overweight (GDMow) show a different metabolic status than women with classic GDM. GDty and GDMow are associated with altered l-arginine/nitric oxide and insulin/adenosine axis signalling in the human foetoplacental microvascular and macrovascular endothelium. These alterations differ from those observed in classic GDM. Here, we have reviewed the consequences of GDty and GDMow in the modulation of foetoplacental endothelial cell function, highlighting studies describing the modulation of intracellular pH homeostasis and the potential implications of NO generation and adenosine signalling in GDty-associated foetal vascular insulin resistance. Moreover, with an increase in the rate of obesity in women of childbearing age worldwide, the prevalence of GDty is expected to increase in the next decades. Therefore, we emphasize that women with GDty and GDMow should be characterized with a different metabolic state from that of women with classic GDM to develop a more specific therapeutic approach for protecting the mother and foetus.
Keywords: adenosine; diabesity; diabetes; intracellular pH; obesity; placenta